Partners' Similarity in Differentiation of Self is Associated With Higher Sexual Desire: A Quantitative Dyadic Study. Issue 7 (2nd October 2016) - Ferreira, Luana Cunha; Narciso, Isabel; Novo, Rosa Ferreira; Pereira, Cícero Roberto
Abstract : The relationship between sexual desire and differentiation of self in couples has been frequently discussed in clinical literature but lacks empirical support. This exploratory study investigates the associations between individual and dyadic levels of sexual desire, differentiation of self, and couple satisfaction. Similarities and discrepancies in sexual desire and differentiation of self between partners were especially targeted. Partners were expected to have a lower discrepancy of differentiation of self than unrelated individuals (Bowen's similarity hypothesis). Partners' discrepancy in differentiation of self was expected to be negatively associated with sexual desire, and higher levels of sexual desire and differentiation in the dyad were expected be positively associated with couple satisfaction. Results suggest that partners' similarity regarding differentiation of self predicted individual sexual desire. Other findings suggest that couple satisfaction was positively associated with both sexual desire and differentiation of self. Limitations and clinical implications are discussed.